2019
DOI: 10.15405/epsbs.2019.12.02.35
|View full text |Cite
|
Sign up to set email alerts
|

The Digital Entrepreneurship As A New Generation Software Of The Mind

Abstract: The Fourth Industrial Revolution as a new technological way of production and services requires a new type of entrepreneurs with a new generation software of the mind as a complex of values, norms and beliefs. In the foreground come out the so-called digital entrepreneurs, whose creative and innovative potential, self-motivation and self-management are the key to business success. The aim of this article is to analyse the value model of digital entrepreneurship via empirical evidence from Bulgaria, using the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The most recent research found the there are no enterprise models to reflect the effect electromagnetic "pollution" that human is exposed to (Garvanova, et al, 2020). The changing business situation requires a new type of value system, including strictly individual and socially defined functions that make their value profile more complex (Garvanova, 2019). A distinctive feature of dynamic management is the ability to generate additional knowledge and innovative solutions in the new conditions of the business environment.…”
Section: Introductionmentioning
confidence: 99%
“…The most recent research found the there are no enterprise models to reflect the effect electromagnetic "pollution" that human is exposed to (Garvanova, et al, 2020). The changing business situation requires a new type of value system, including strictly individual and socially defined functions that make their value profile more complex (Garvanova, 2019). A distinctive feature of dynamic management is the ability to generate additional knowledge and innovative solutions in the new conditions of the business environment.…”
Section: Introductionmentioning
confidence: 99%